Influence of phosphate ion dopant on corrosion protection properties of polypyrrole coatings on carbon steel - Sabouri, M.; Shahrabi, T.; Faridi, H.; Salasi, Mobin (Maney Publishing, 2009)
Polypyrrole (PPy) and polypyrrole-phosphate (PPyP) coatings were electropolymerised onto carbon steel electrodes in aqueous oxalic acid solution using the cyclic voltammetry technique. The electropolymerisation of PPyP was carried out with addition of trisodium phosphate to the supporting electrolyte. Prepared coatings were characterised using scanning electron microscopy. In addition, the ability of the coatings to control the corrosion of carbon steel was studied with the help of a variety of electrochemical methods: open circuit potential monitoring, potentiodynamic polarisation and electrochemical impedance spectroscopy all in 3?5% NaCl solution. All the results have consistently indicated that carbon steel is better protected by the PPyP coating than by the PPy coating. © 2009 Institute of Materials, Minerals and Mining.